Evaluation of heat-storage system based on CHP-plant fuel oil tanks - Makhotilo K.V. (General Energy Institute of the National Academy of Sciences of Ukraine, 2008)
Results of technical and economical assessment of a heat-storage system based on fuel oil tanks of CHP-plant as well as its application expediency in case of the CHP-plant used a bidding strategy to compete on wholesale electricity market are presented. Calculations are performed using data related to basic operation modes of Kharkiv CHP-plant #5. Time intervals and volumes of thermal energy accumulation as well as parameters and quantity of required heat exchangers and fuel oil pumps are determined.